Recurrent dislocation: scientific evidence and management following a systematic review. Issue 7 (July 2017) - Melo, A.R.; Pereira Júnior, E.D.; Santos, L.A. de M.; Vasconcelos, B.C. do E.
Abstract: Recurrent mandibular dislocation is a rare condition that can have a negative impact on quality of life. Different surgical techniques are employed in the treatment of this condition, and the demand for maximum healthcare quality has contributed to the implementation of evidence-based clinical practice. The objective of this study was to determine the level of scientific evidence in articles reporting open surgical treatment for recurrent mandibular dislocation. A comprehensive search strategy was conducted to locate relevant articles in the PubMed and Web of Science databases on open surgical treatment for recurrent mandibular dislocation published between January 1974 and August 2014. These were classified into one of the five established levels/sublevels of evidence: the level of evidence was determined based on the classification proposed by the Oxford Centre for Evidence-Based Medicine. One hundred and fourteen articles were identified, 91 of which were excluded based on the eligibility criteria. Thus, 23 articles were selected for inclusion in the review. All of the selected articles were rated as level 4 (low quality) regarding the level of evidence. The present review revealed that articles on open surgical treatment for recurrent mandibular dislocation exhibit a low level of scientific evidence. Thus, further studies on this topic with greater methodological rigour are needed.